ホッキョク カイ カイヒョウ イキ ニ オケル キソ セイサン ト エネルギー イドウ ノ ジケイレツ テキ ヘンドウ ノ ケンキュウ PREFLA ケイカク - 福地, 光男; フクチ, ミツオ; 内藤, 靖彦; ナイトウ, ヤスヒコ; 星合, 孝男; ホシアイ, タカオ; Fukuchi, Mitsuo; Naito, Yasuhiko; Hoshiai, Takao (1990)
P(論文) 「北極海海氷域における基礎生産とエネルギー移動の時系列的変動の研究」("PREFLA"計画)は, 昭和63年度から平成2年度までの3年計画であり, 文部省科学研究費・国際学術研究として実施されている。本計画は, 季節的に海氷におおわれる北極海域において, 基礎生産過程およびその深層への沈降過程を時系列的に明らかにすることを目的とする。同時に, エネルギー移動の過程における動物プランクトンの役割を明らかにするものである。南極沿岸域との比較を念頭におき, 調査海域として, 北部ベーリング海とチャクチ海を選んだ。本計画はアメリカ合衆国が同海域で実施している「大陸棚上における物質・エネルギーの移送と循環」計画("ISHTAR"計画)と協同で実施されている。本研究計画の概要と昭和63年・平成元年の野外調査概要をまとめた。 "Temporal variability of primary production and energy flow in Arctic sea ice area (PREFLA)" is a three-year program of 1988-1990,which is supported with a grant under the Monbusho International Scientific Research Program. The program aims to clarify the temporal variations of primary production and its downward flux as well as to evaluate the role of zooplankton in energy flow. The northern Bering Sea and the Chukchi Sea are selected to compare the ice-associated biological process in the Antarctic coastal areas. The program cooperates with the U. S. program of "Inner Shelf Transfer and Recycling (ISHTAR)". Three field observations were made in 1988 and the other two observations were done in 1989. departmental bulletin paper